The role of business and organized labor in the maintenance of private health insurance in the United States - Sauviat , Catherine (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2024)
Business and organized labor in the US have been historically involved in health insurance through employment, in absence of a universal health care system. This employment-based healthcare system remains the dominant form of coverage for Americans today although its importance has been declining over the long-term. Over the last decade and after the passage of the Affordable Care Act, employers and unions have sometimes been challenging the system. But the convergence toward a universal system is likely to be a long process.